Predictive Analytics and Retrieval Using Mri-A Recent Retrospective - Jasmine, R. A; Rani, P. A. J; Sharmila, D.J (International Journal of Computer Sciences and Engineering, 2025)
Research in MRI is gaining attention for tumor detection, classification, retrieval which it is critical for diagnosis, surgical planning and treatment. Several techniques are proposed to address this challenge and none of the solution is yet perfect. The accuracy of the system is improved using pre-processing, determined in feature extraction, evaluated in classification and retrieval techniques. Segmentation techniques are used to extract the tumor for feature extraction. As the tumor characteristic differs on various types, different spatial, wavelet, model based techniques are adapted to capture the unique features. The objective of this paper is to present a comprehensive overview of different methods, their efficacy on predictive analytics and retrieval.